2012
DOI: 10.1186/1471-2393-12-48
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis for neonatal sepsis in southeastern Mexico: analysis of a four-year historic cohort follow-up

Abstract: Background Neonatal sepsis is a worldwide public health issue in which, depending on the studied population, marked variations concerning its risk and prognostic factors have been reported. The aim of this study was to assess risk and prognostic factors for neonatal sepsis prevailing at a medical unit in southeastern Mexico. Thus, we used a historic cohort design to assess the association between a series of neonates and their mothers, in addition to hospital evolution features and the risk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
102
7
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(163 citation statements)
references
References 44 publications
41
102
7
13
Order By: Relevance
“…Thus, it is not just PPROM that is associated with neonatal sepsis, but the decrease in the volume of AF also favors perinatal infection. 8,19,20 We can also point out the difficulty in diagnosing chorioamnionitis because adverse perinatal outcomes often occur without clinical or laboratory signs of infection. 1,17 Authors analyzing the placentas of puerperal woman who had PROM found a poor correlation between histological chorioamnionitis (59%) and clinical chorioamnionitis (42%).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not just PPROM that is associated with neonatal sepsis, but the decrease in the volume of AF also favors perinatal infection. 8,19,20 We can also point out the difficulty in diagnosing chorioamnionitis because adverse perinatal outcomes often occur without clinical or laboratory signs of infection. 1,17 Authors analyzing the placentas of puerperal woman who had PROM found a poor correlation between histological chorioamnionitis (59%) and clinical chorioamnionitis (42%).…”
Section: Discussionmentioning
confidence: 99%
“…But the gold standard for diagnosing early onset sepsis is the isolation of causative organism from blood. 4 Worldwide, the neonatal mortality rate varies from 2.8 to 4 million deaths each year with 95% of the deaths occurring indeveloping countries 5 Refusal to feed and jaundice were the most common findings, being present in 77(64.2%) each of the studied cases (Table -3 Various maternal factors which showed statistical significance with mortality were maternal fever (p= 0.032), primiparity (p= 0.013), prolonged rupture of membrane (PROM) >18 hours (p=0.006), meconium stained amniotic fluid (p=0.007), maternal age< 20yrs (p= 0.000), foul smelling liquor (P= 0.000)[ I/T ratio -immature to total neutrophil ratio; CRP -C-reactive protein; ESR -erythrocyte sedimentation rate…”
Section: Introductionmentioning
confidence: 99%
“…This was higher to that reported in previous studies done in India and Mexico. 11,12 The higher rate of sepsis is due to illiteracy, low socioeconomic condition and due to poor antenatal care. In our study there was male predominance almost double to female because of sex specific custom practiced in the society, higher proportion of males were brought to the hospital and the locus of the gene for synthesis of immunoglobulins lies at X-chromosome.…”
Section: Discussionmentioning
confidence: 99%